Intervención del terapista respiratorio en paciente masculino de 53 años de edad con neumonía adquirida en la comunidad. - Cabezas Vargas, Jeffrey Fabricio (2022)
Community-acquired pneumonia is an infiltration of the lung by pathogenic agents, mainly by the bacterium Streptococcus pneumoniae, and has become a mess to resolve; In general, it is more common in patients over 60 years of age and under 8 years of age, because they have lung problems or are patients with a low immune system. Complications of pneumonia occur when the infection is not limited to the lung parenchyma but spreads to nearby areas or when the progression of the infection is more complex than usual for various reasons. Complications of CAP are: pneumothorax, pleural effusion, bronchopleural fistula, lung abscess. The present case study is focused on a 53-year-old male patient who presented dyspnea on minimal exertion, tachypnea, thermal rise and spontaneous respiratory rate 34 rpm with an evolution of 5 days and was diagnosed with community-acquired pneumonia. The treatment consists of antimicrobial therapy, low and high flow oxygen therapy, non-invasive and invasive mechanical ventilation, it is very essential in the management of community-acquired bacterial pneumonia, oxygen therapy.